The wedding [compact disc, unabridged] - Sparks, Nicholas (Time Warner AudioBooks, 2003)
Wilson Lewis knows that the romance has gone out of his marriage so as he prepares for his daughter's wedding he seeks a way to make his wife Jane fall in love with him again.